2010
DOI: 10.1063/1.3286436
|View full text |Cite
|
Sign up to set email alerts
|

Growth and saturation of the axial instability in low wire number wire array Z pinches

Abstract: The growth of the axial instability in low wire number wire array Z pinches using a 100 ns rise time, 1 MA pulsed power accelerator is examined. The axial instability manifests itself as a quasiperiodic variation of the radius of the coronal plasma along each wire and a consequent modulation of the rate of ablation of material from the dense wire core. The dominant wavelength of the modulation becomes constant late in time. In this work laser shadowgraphy is used to measure the growth of the wavelength and amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…At the same time, as validly mentioned by the authors of Ref. 6, the small university setups, allowing low-cost experimentation, are well suited for testing both new diagnostics [6][7][8][9] and new schemes for realization of proper initial conditions in imploding plasma shells in Zpinch experiments.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…At the same time, as validly mentioned by the authors of Ref. 6, the small university setups, allowing low-cost experimentation, are well suited for testing both new diagnostics [6][7][8][9] and new schemes for realization of proper initial conditions in imploding plasma shells in Zpinch experiments.…”
Section: Introductionmentioning
confidence: 93%
“…Hence, the wire array should consist of 5-15 wires spaced some parts of a centimeter or even several centimeters apart. When the distance between the wires is large, severe ablation occurs at the wire surface, 7,8 which reduces both the implosion velocity and the radiation power of the Z-pinch.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, once the ablation streams from the wires have developed, they present axial modulations with a typical wavelength dependent on the wire material (k $ 0.5 mm for Al, k $ 0.25 mm for W), which is a consequence of the global field topology that swept the coronal plasma accumulated in the vicinity of the wires away from them. 11,12 Furthermore, it has been found that these streams can be narrowed by the field penetration within the array and its curvature close to each wire. 13 The ablation dynamics in wire arrays is not only important because of their influence on the implosion, as it determinates the x-ray emission from these configurations 1,6,14 but also is interesting object to study collisionality processes in dense magnetized supersonic plasma flows.…”
Section: Introductionmentioning
confidence: 99%
“…In wire array implosions axial nonuniformity of wire ablation results in plasmas colliding on the axis at a time that depends on axial position and a consequence decrease in implosion symmetry [5]. In the case of solid liner implosions, the magneto-RayleighTaylor (MRT) instability results in breakup of liner which has been taken as the greatest threat to MagLIF.…”
Section: Introductionmentioning
confidence: 99%